2022
DOI: 10.1039/d2gc01772e
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the oxidative esterification of 5-hydroxymethylfurfural to furan-2,5-dimethylcarboxylate

Abstract: 5-Hydroxymethylfurfural (HMF) as an important versatile compound derived from renewable biomass gained great significance in both industry and academia. The oxidative esterification product of HMF: furan-2,5-dimethylcarboxylate (FDMC) is considered to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…To date, only catalysts containing Co, Pd, and Au species have been reported as effective materials for the oxidative esterification of HMF. 6 For instance, Fu et al reported a system containing Co x O y −N@C and K-OMS-2 with the base of K 2 CO 3 , resulting in DMFD and monomethyl-2,5-furan dicarboxylate (MMFD) yields of 50 and 40%, respectively. 7 Catalyst combinations such as CoO x -N/C + MnO 2 and Co x O y -N/C + Ru/C have also been reported to achieve high DMFD yields (>95%).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only catalysts containing Co, Pd, and Au species have been reported as effective materials for the oxidative esterification of HMF. 6 For instance, Fu et al reported a system containing Co x O y −N@C and K-OMS-2 with the base of K 2 CO 3 , resulting in DMFD and monomethyl-2,5-furan dicarboxylate (MMFD) yields of 50 and 40%, respectively. 7 Catalyst combinations such as CoO x -N/C + MnO 2 and Co x O y -N/C + Ru/C have also been reported to achieve high DMFD yields (>95%).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Among them, DFF plays a pivotal role as a crucial chemical intermediate for the synthesis of antibiotics, 12 fluorescent dyes, 13 adhesives and biomass-based resins. 14 Although many HMF oxidation catalysts have been studied and reported, [15][16][17][18][19][20][21][22][23][24] the selective transformation of HMF into DFF presents a considerable challenge due to the existence of multiple parallel oxidation reaction pathways and overoxidation of DFF. Moreover, harsh reaction conditions including elevated temperatures and pressures further increase the actual cost.…”
Section: Introductionmentioning
confidence: 99%
“…26 HMFCA a comparatively less known oxidative product of HMF, is considered to produce furanic polyesters which can substitute those obtained from fossil sources 27 and to synthesize interleukin inhibitors. 28 It also possesses anti-tumoral activities. 29 Currently, oxidation of HMF to several value-added products is typically performed under hydrothermal, [30][31][32] photocatalytic, 33 bio-catalytic, heterogeneous or homogeneous catalytic conditions, 34 and electrochemical oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…26 HMFCA a comparatively less known oxidative product of HMF, is considered to produce furanic polyesters which can substitute those obtained from fossil sources 27 and to synthesize interleukin inhibitors. 28 It also possesses anti-tumoral activities. 29…”
Section: Introductionmentioning
confidence: 99%